2022
DOI: 10.1021/acsapm.2c01484
|View full text |Cite
|
Sign up to set email alerts
|

Protein-Resistant Amphiphilic Copolymers Containing Fluorosiloxane Side Chains with Controllable Length

Abstract: Molecular-scale compositional heterogeneities can slash the nonspecific interaction between proteins and surfaces, resisting surface contamination. In this work, an amphiphilic copolymer containing a soft fluorosilicone macromonomer with controllable chain length as low-surface-energy hydrophobic component and a zwitterionic monomer as hydrophilic component was prepared to establish molecular-scale compositional heterogeneities. The length of the fluorosiloxane side chains can significantly impact the surface … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 41 publications
0
5
0
Order By: Relevance
“…In addition, the fouling release ability of low-surface-energy materials can be effectively improved by grafting functional groups, such as amphiphiles, PEGs and quaternary ammonium salts, on PDMS or by preparing fluorosilicone co-modified materials. Wang et al [ 30 ] designed an amphiphilic copolymer with fluorosilicone macromonomers as hydrophobic soft-side chains and amphiphiles as hydrophilic hard-side chains ( Figure 6 ). The results showed that the coating retained plenty of low-surface-energy fluorosilicone segments on the surface even underwater, giving full play to the synergistic effect of the amphiphilic polymer while exhibiting excellent resistance to various proteins.…”
Section: New Environmentally Friendly Antifouling Coatingmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, the fouling release ability of low-surface-energy materials can be effectively improved by grafting functional groups, such as amphiphiles, PEGs and quaternary ammonium salts, on PDMS or by preparing fluorosilicone co-modified materials. Wang et al [ 30 ] designed an amphiphilic copolymer with fluorosilicone macromonomers as hydrophobic soft-side chains and amphiphiles as hydrophilic hard-side chains ( Figure 6 ). The results showed that the coating retained plenty of low-surface-energy fluorosilicone segments on the surface even underwater, giving full play to the synergistic effect of the amphiphilic polymer while exhibiting excellent resistance to various proteins.…”
Section: New Environmentally Friendly Antifouling Coatingmentioning
confidence: 99%
“…Figure 6. Antifouling mechanism of amphiphilic copolymers[30] with permission (Copyright © 2023, American Chemical Society).…”
mentioning
confidence: 99%
“…A crucial initial step in macrofouling is the successful adsorption of organic compounds, such as proteins, polysaccharides, and nucleic acids, onto underwater substrates. Hydrophilic antifouling coatings operate by capitalizing on the inhibitory effect of the surface hydration layer on the adsorption of organic macromolecules, which discourages subsequent attachment by fouling organisms [38]. Consequently, evaluating the anti-protein-adsorption capacity of antifouling coatings is essential for assessing their fouling resistance.…”
Section: Surface and Physicochemical Properties Of The Coatingsmentioning
confidence: 99%
“…Additionally, it demonstrates certain capabilities for releasing dirt. The research team led by Professor Lingmin Yi at Zhejiang University of Technology [47] developed an amphiphilic polymer. This polymer is composed of a flexible fluorosilicon macromonomer, which serves as the hydrophobic component with a low surface energy, and an amphiphilic monomer, which acts as the hydrophilic component.…”
Section: Fouling Release Antifouling Coatingsmentioning
confidence: 99%
“…This agent was prepared by utilizing polycaprolactone-based (PCL) polyurethane as a carrier, enabling a gradual and regulated release of the antifouling agent due to the biodegradable properties of the resin. The experimental results, depicted in Figure 5B, demonstrated that the developed agent exhibited a certain level of antifouling efficacy against larvae of ma- [51]; (B) Antifouling mechanism of amphiphilic copolymer [47] with permission (Copyright © 2023, American Chemical Society).…”
Section: Bionic Antifouling Coatingsmentioning
confidence: 99%